Phosphorus Saturation Indices as a Measure of Risk of P Loss for Some Major Indian Soils - V.R. Ramkrishana Parama, I. Rashmi, A.K. Biswas (Journal of the Indian Society of Soil Science, 2016)
Phosphorus (P) movement via surface or sub-surface pathways often lead to P loss from agricultural soils and contribute to eutrophication of surface water bodies. The aim of this study was to develop an index based on degree of P saturation (DPS) for some major Indian soils through routine soil testing P methods. The DPS values were calculated in soils saturated to different extent of P with respect to P sorption maxima (Psmax). Phosphorus sorption capacities of the studied soils were high with the average value of 600 mg kg-1. The critical threshold values of DPS (>20%) varied from soil to soil type and also with extractants. The DPS threshold values for black soils were 21.7, 21.3 and 23.4%, respectively for Olsen, ammonium oxalate (AO) and Mehlich 3 (M3) extractants at 100 and 200% Psmax treatments. In alluvial soils the threshold P saturation values were recorded higher than black soil and was 29.1 and 29%, respectively for Olsen and M3 at 50 and 200% Psmax treatments. On the other hand in acid soils Bray based DPS was higher (33.1%) than AO (22.6%) and M3 (27.6%) at 100 and 200% Psmax treatments. Routine soil test P (STP) along with environmental indices like DPS integrated with crop management and site properties can characterise risk of P loss more accurately from agricultural land.